Peran Lembaga Pemasyarakatan Dalam Pembentukan Kesadaran Narapidana di Bima NTB - S, Sukirman; N, Nasrullah; J, Jufrin; Amin, Muhamad; A, Ahmad; Imaduddin, M Asad; Sagaf, Umar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted by analyzing the role of correctional institutions in forming the awareness of prisoners in Bima NTB and the obstacles experienced by correctional institutions in forming the awareness of prisoners in Bima NTB. The type of research used in this research is empirical law or non-doctrinal legal research, namely the type of research that will focus on examining field realities and combining them with legal rules, legal principles and legal norms contained in statutory regulations or positive law. The results of the research show that the role of correctional institutions in forming awareness of prisoners in Bima, NTB, correctional development of prisoners in Bima detention center has been carried out very well, considering that all training activities carried out in prisons are activities that have been determined by the laws and regulations relating to prisons and Coaching, in other words, coaching in the detention center has been carried out in a structured manner with a correctional system that upholds the elements of education and character building for prisoners as the main focus of coaching. The efforts made in providing guidance to prisoners are shared by all prisoners from skills activities and providing seminars for prisoners to inspire their minds to change and live a better life, both spiritually and physically. Apart from that, the obstacles faced by supervisors in carrying out community development for prisoners at the Bima Detention Center are limited time and human resources, namely the ability of a supervisor to carry out guidance. Facilities and infrastructure that meet the criteria but are still less efficient in their use due to situations and conditions that sometimes prevent prisoners from using some facilities.